Analisis Hukum Pelanggaran Lalu Lintas oleh Pelajar dan Upaya Penanggulangannya di Wilayah Hukum Polres Langkat - Efendi, Efendi; Ahmad, Akiruddin; Akmal, Akmal; Simanjorang, Marulita (Journal of Law & Policy Review, 2025)
This study aims to analyze the factors contributing to traffic violations among junior high school students and to examine the countermeasures implemented by the Langkat Police. The research employs a normative-empirical legal approach, combining analysis of statutory regulations with empirical field data. The findings reveal that various factors, including low legal awareness, negligence, lack of knowledge of regulations, and family and social environments, influence traffic violations among students. The most common violations include not wearing helmets, not possessing a valid driving license, and incomplete vehicle documentation. The countermeasures undertaken by the Police include pre-emptive, preventive, and repressive approaches. These efforts have helped reduce the number of violations; however, their effectiveness largely depends on the synergy among law enforcement agencies, families, and educational institutions. Therefore, a collaborative and sustainable approach is required to enhance legal awareness and establish a culture of traffic discipline among students.